ANALISIS KELAYAKAN BISNIS USAHA JAJANAN CIMOL TAHU KENTANG BERSAUDARA DI PALU - Muhammad Widyatama; Mohamad Raffi Cendika Putra; munawarah; Muhammad Din (Publika Citra Media, 2026)
This study analyzes the investment feasibility of the Cimol Tahu Kentang Bersaudara business in Palu City using a descriptive quantitative method using Present Value (PV), Net Present Value (NPV), Profitability Index (PI), Payback Period (PBP), Internal Rate of Return (IRR), and Average Rate of Return (ARR) indicators. Data comes from estimated investment costs, operations, revenue, and three-year cash flow projections. The analysis results show a PV of Rp1,592,875,325 and an NPV of Rp1,542,875,325, indicating significant profits. PI > 1 reflects efficiency, PBP of only 0.09 years (±33 days) indicates a fast return on investment, IRR of 10–11% exceeds the benchmark interest rate, and ARR of 1,176%–2,352% indicates high profit potential. Thus, this business is declared very financially feasible and has long-term prospects.